THE utilization OF JUICE Morinda citrifolia AND Averrhoa bilimbi AS A LATEX EMULSIFIER AGENT - Marlina Kamelia; Khairul Anam; Netriwati Netriwati; Rina Budi Satiyarti; Dwijowati Asih Saputri; Nurhaida Widiani (Biota, 2021)
The area of rubber land in Indonesia currently reaches 3,672,213 ha which can produce 3,229,861 tons/year. The price of rubber in Indonesia is currently cheap because of low-quality latex. The low quality of latex is caused by the large production costs, one of which is the price of latex clotting material which is relatively expensive. Therefore, this studied aims to find a good alternative to latex coagulant but at low cost. Latex clumping material used in this research were noni juice and star fruit. The treatment in this study used noni juice and star fruit juice concentration of 5 ml, 10 ml, 15 ml, and 20 ml, respectively. The results showed the weight of latex with noni emulsifying agents increased by 45.58% while the administration of star fruit juice was not much different, amounting to 45.70%. However, the final weight of latex given by the emulsifying agent in the form of star fruit was higher than Noni with the difference at the highest weight reached 4.23 grams. The fastest latex clumping time at 20 ml star fruit concentration is 1.18 minutes. Based on research results noni juice and star fruit potential as a latex clot.